(untitled) (Research, Society and Development, 2022)
This study presents an excerpt of the studies developed in a Professional Master’s Degree in Education, linked to a university located in the extreme south of Brazil. The objective was to identify the perception of educators from a bilingual school about education for ethnic-racial relations and to verify which themes/methodologies they consider fundamental to work with Libras and ethnic-racial relations at school. Methodologically, it is classified as qualitative in nature and procedurally it is a case study, in which a semi-structured questionnaire was used as an instrument for data collection. Results indicate that despite knowing the legislation and knowing that it is mandatory, most did not have initial or continuing training to develop the theme in the classroom. It is also pointed out that educational games and games were the main themes highlighted as fundamental for approaching Libras and ethnic-racial relations. Finally, we emphasize how fundamental it is to encourage research and the production of pedagogical materials on education for ethnic-racial relations in bilingual schools.